Vitamin A-treated natural killer cells reduce interferon-gamma production and support regulatory T-cell differentiation - Jeong, Mingeum; Cortopassi, Francesco; See, Jia-Xiang; Torre, Carolina de la; Cerwenka, Adelheid; Stojanovic, Ana (European journal of immunology, 2024)
Natural killer (NK) cells are innate cytotoxic lymphocytes that contribute to immune responses against stressed, transformed, or infected cells. NK cell effector functions are regulated by microenvironmental factors, including cytokines, metabolites, and nutrients. Vitamin A is an essential micronutrient that plays an indispensable role in embryogenesis and development, but was also reported to regulate immune responses. However, the role of vitamin A in regulating NK cell functions remains poorly understood. Here, we show that the most prevalent vitamin A metabolite, all-trans retinoic acid (atRA), induces transcriptional and functional changes in NK cells leading to altered metabolism and reduced IFN-γ production in response to a wide range of stimuli. atRA-exposed NK cells display a reduced ability to support dendritic cell (DC) maturation and to eliminate immature DCs. Moreover, they support the polarization and proliferation of regulatory T cells. These results imply that in vitamin A-enriched environments, NK cells can acquire functions that might promote tolerogenic immunity and/or immunosuppression.